O componente curricular arte no ensino médio integrado dos Institutos federais: uma possibilidade de integração com a educação profissional e tecnológica (Revista Educação, Artes e Inclusão, 2024)
The present article aims to present a pedagogical practice that helps to promote the integration between the arts curriculum and vocational and technological education in the integrated high school offered by the Federal Institutes of Educational Science and Technology in Brazil, consid-ering the perspective of human formation and focusing on one of its aspects, work as a pedagog-ical principle. To this end, the conceptual foundations of this type of education are objectively pre-sented, the concept of work as an educational principle is discussed, a brief explanation of the characteristics of counter-hegemonic arts education (with influence from the triangular approach of Ana Mae Barbosa) is given, and the conceptual and ideological similarities and approximations between arts education and professional education, which aims to be omnilateral and emanci-pated, are discussed. Finally, a proposal is presented to illustrate the feasibility of integration be-tween artistic and technical learning. It concludes that this integration is possible if the art educator knows and masters the conceptual foundations of professional and technical education and acts pedagogically with ethical and political commitment.
Keywords: art; vocational education; integration